DIFFICULTIES IN LEARNING ENGLISH AS A SECONDARY LANGUAGE IN THE SAUDI ARABIAN EDUCATION SYSTEM - Zaidi, Hina Ali (International Journal of Research -GRANTHAALAYAH, 2018)
English as an additional language is inevitable in the Saudi Arabian education system. This study is an analysis of some of the causes of English learning problems. The goals of the study were to find out the root cause of the problems in learning English; to find out if there was a significant difference in the causes of the problems that students were comparing due to various attributive variables such as gender, location, habit of reading English daily newspapers, and a habit of listening to English news. The methodology for collecting information was a survey method. The sample consisted of 500 students with 307 boys and 193 girls. The data collected was analyzed. The result of this study showed that the environment was the main cause of learning English. Boys had more problems compared to girls. Another important finding was that rural students felt more problems than urban students.